Comercialização de alimentos: convergências entre agroecologia e economia solidária - Poncio, Aline (Universidade Federal de São Carlos, 2025)
Family farming is extremely relevant and strategic for Brazil, playing a fundamental role in food production and local development. In recent years, initiatives aimed at expanding its autonomy and presence in markets have been strengthened through the creation of alternative forms of commercialization. Increasingly, farmers are developing alternative approaches to market food, while at the same time organizations are emerging that seek new forms of consumption and prioritize solidarity-based relationships. The commercialization of food using principles of solidarity economy arises as an alternative to conventional markets, seeking a more equitable and fair socioeconomic relationship among farmers, intermediaries, and consumers. This research aimed to understand how solidarity economy has been studied in different agricultural contexts through bibliometric analysis and, through a case study, to present the incubation process and the operation of a market that applies solidarity economy principles in food commercialization and organizational structure, which may serve as a model and alternative in different localities.
Food marketing: convergences between agroecology and solidarity economy
Keywords: Economia solidária; Tecnologia social; Agroecologia; Solidarity economy; Social technology; Agroecology; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA